Composition rules of Ni-base single crystal superalloys and its influence on creep properties via a cluster formula approach - Chen Chen (Nature Portfolio, 2020)
Abstract The present work investigated the composition evolution of the TMS series of Ni-base single crystal (SC) superalloys in light of the cluster formula approach systematically. The cluster formula of SC superalloys could be expressed with $${[}\overline{{{\text{Al}}}} {-} \overline{{{\text{Ni}}}} 12{](}\overline{{{\text{Al}}}} {, }\overline{{{\text{Cr}}}} {)}m$$ [ Al ¯ - Ni ¯ 12 ] ( Al ¯ , Cr ¯ ) m , in which all the alloying elements were classified into three groups, Al series ( $$\overline{{{\text{Al}}}}$$ Al ¯ ), Cr series ( $$\overline{{{\text{Cr}}}}$$ Cr ¯ ), and Ni series ( $$\overline{{{\text{Ni}}}}$$ Ni ¯ ). It was found that the total atom number (Z) of the cluster formula units for TMS series of superalloys varies from Z ~ 17 to Z ~ 15.5, and then to Z ~ 16 with the alloy development from the 1st to the 6th generation, in which the superalloys with prominent creep resistance possess an ideal cluster formula of $${[}\overline{{{\text{Al}}}} {-} \overline{{{\text{Ni}}}} 12{](}\overline{{{\text{Al}}}} 1.5\overline{{{\text{Cr}}}} 1.5{)}$$ [ Al ¯ - Ni ¯ 12 ] ( Al ¯ 1.5 Cr ¯ 1.5 ) with Z = 16. Similar tendency of composition evolution also appears in the PWA and CMSX series of SC superalloys. Typical TMS series of superalloys with prominent creep properties generally exhibit a moderate lattice misfit of γ/γ′ which could render alloys with appropriate particle size of cuboidal γ′ precipitates to acquire a maximum strength increment by precipitation strengthening mechanism. More importantly, the relationship between the lattice misfit (δ) of γ/γ′ and the creep rupture lifetime (t r ) of superalloys was then established, showing a linear correlation in the form of lgt r –lg|δ|3/2 at both conditions of 900 °C/392 MPa and 1100 °C/137 MPa. Combined with the lattice misfit, the cluster formula approach would provide a new way to modify or optimize the compositions of Ni-base superalloys for further improvement of creep property.